Application of the Principle in Absentia in the Election of Regional Heads - Asyawati Kasim (SEAN Institute, 2025)
This study aims to analyze the application of the principle of in absentia in the election of regional heads (pilkada) in Indonesia. The research method used is normative law with a conceptual approach and analysis of laws and regulations, case studies, and empirical research results. The study identifies variations in interpretation and implementation in absentia between regions, evidentiary challenges, potential human rights violations, and their effectiveness in law enforcement. The results of the study show that the implementation of in absentia can accelerate the handling of election crimes, but also pose a risk of human rights violations and legal uncertainty. Policy recommendations include harmonization of regulations, strengthening the authority of Bawaslu, improving coordination of Gakkumdu, increasing resource capacity, strict supervision, as well as education and socialization to ensure the implementation of in absentia that is fair, accountable, and in accordance with the principles of the rule of law. This study concludes that the implementation of in absentia in regional elections requires serious attention to the legal basis, implementation practices, and its impact on human rights and the quality of democracy.